On the Relationship Between Authentic Leadership, Flourishing, and Performance in Healthcare Teams: A Job Demands-Resources Perspective - Marques-Quinteiro, Pedro; Graça, Ana Margarida; Coelho, Francisco Antonio; Martins, Daniela (Frontiers in Psychology, 2021)
This study integrates the job demands-resources model and authentic leadership theory to test the general hypothesis that authentic leadership is a job resource that enables flourishing and performance in healthcare teams. Furthermore, this article tests the hypothesis that the daily bed occupancy is a job demand that weakens this relationship. Participants were 106 nurses that were distributed across 33 teams from two hospitals. The results suggest that the authentic leadership of team leaders is positively related with subjective and objective team performance, but only when daily bed occupancy is low. Authentic leadership had no relationship with team flourishing, regardless of the daily bed occupancy. Our findings suggest that the extent to which authentic leadership is adequate to promote the performance of teams working in a hospital setting is sensitive to contextual boundary conditions. Leading authentically might only be effective under specific circumstances.